2018
DOI: 10.26811/peuradeun.v6i3.214
|View full text |Cite
|
Sign up to set email alerts
|

Educational Revitalization of the Children with Special Needs at an Inclusive School

Abstract: The main purpose of this research is to find out the forms and meaning of revitalization of children with special needs at an inclusive school, particularly at Saraswati Elementary School, Tabanan, and Bali. This research is a qualitative research with an approach of a Cultural Study. The results show that the forms of revitalization are increasing resources, such as the workshop of teachers and students parents; providing apprentice for school staff, especially the manager of school library; increasing the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Research conducted by Adhi & Seniwati found the form and meaning of revitalization for children with special needs in inclusive schools, especially at SD Saraswati Tabanan and Bali. The results of the research show that a form of revitalization is an increase in resources, such as workshops for teachers and students' parents; providing apprenticeships for school staff, particularly school librarian managers; increasing the involvement of children with special needs with other peers in self-development; complementing facilities such as special guidance rooms and library facilities (Adhi & Seniwati, 2018).…”
Section: A Introductionmentioning
confidence: 99%
“…Research conducted by Adhi & Seniwati found the form and meaning of revitalization for children with special needs in inclusive schools, especially at SD Saraswati Tabanan and Bali. The results of the research show that a form of revitalization is an increase in resources, such as workshops for teachers and students' parents; providing apprenticeships for school staff, particularly school librarian managers; increasing the involvement of children with special needs with other peers in self-development; complementing facilities such as special guidance rooms and library facilities (Adhi & Seniwati, 2018).…”
Section: A Introductionmentioning
confidence: 99%